Assessing the impact of referred actions on protected matters under Australia's national environmental legislation. Issue 1 (14th December 2022) - Maitz, Natalya M.; Taylor, Martin F. J.; Ward, Michelle S.; Possingham, Hugh P.
Abstract: Australia's national environmental legislation, the Environment Protection and Biodiversity Conservation Act 1999 (EPBC Act) has been criticized for failing to mitigate the national extinction crisis. Under the EPBC Act, projects anticipated to have a significant impact on protected matters must be referred to the Australian Government for assessment. Actions deemed unlikely to have a significant impact are granted permission to proceed, while actions expected to have a significant impact must undergo further assessment. We spatially analyzed potential habitat loss deemed either significant or non‐significant in Queensland and New South Wales for threatened species, migratory species, and threatened ecological communities between 2000 and 2015. Impact scores were developed to quantify and compare the value of woody vegetation cleared under each referral determination. We found no statistically significant difference between median impact scores for vegetation removed under significant and non‐significant determinations. Over half (63%) of all scored losses occurred under actions deemed non‐significant, with certain species disproportionately impacted. The tiger quoll ( Dasyurus maculatus maculatus ) and grey‐headed flying‐fox ( Pteropus poliocephalus ) lost 82% and 72% of their total referred potential habitat under non‐significant actions, respectively. Our results indicate that the application of the EPBC Act is failing to adequately conserve the protected matters of this investigation. Abstract : Our spatial analysis explores the consequences of referral determinations on protected matters under Australia's environmental legislation, the EPBC Act. We compare the impacts of "controlled action" and "not controlled action" determinations on land clearing related actions in Queensland and New South Wales. Contrary to expectations, no significant difference is found between the impacts of "controlled action" and "not controlled action" determinations on threatened habitats.